2009
DOI: 10.1186/1744-9081-5-42
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of postural sway in high anxious children

Abstract: Background: Current research suggests that elevated levels of anxiety have a negative impact on the regulation of balance. However, most studies to date examined only global balance performance, with little attention to the way body posture is organized in space and time. The aim of this study is to examine whether posturographic measures can reveal (sub)clinical balance deficits in children with high levels of anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 33 publications
2
39
1
1
Order By: Relevance
“…Each dot shows an individual's mean score for the two variables. afferent processing [28][29][30] and the midcingulate cortex, a pivotal node of interaction between negative emotions and motor signals that trigger defensive responses [31].…”
Section: Discussionmentioning
confidence: 99%
“…Each dot shows an individual's mean score for the two variables. afferent processing [28][29][30] and the midcingulate cortex, a pivotal node of interaction between negative emotions and motor signals that trigger defensive responses [31].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that regulation of balance is attention demanding, even in highly skilled individuals such as dancers [21]. We tested the effect of an attention demanding cognitive activity on postural fluctuations in a group of children with a mild form of ASD, using a word memorization task [21,22]. If individuals with ASD employ excessive cognitive resources to regulate their balance, then cognitive dual-tasking should have a destabilizing effect on this group but not on controls.…”
Section: Introductionmentioning
confidence: 99%
“…In our case, the total length (Stins, Ledebt, Emck, Dokkum, & Beek, 2009;Teranishi et al, 2011) of trajectory (TL) is used to evaluate an angle-angle plot. The total length of pitch vs. roll is computed by calculating the sum of the Euclidean distances between consecutive data points (i.e.…”
Section: Discussionmentioning
confidence: 99%